14N Solid‐State NMR Spectroscopy of Amino Acids. Issue 23 (31st October 2016) - Veinberg, Stanislav L.; Friedl, Zachary W.; Lindquist, Austin W.; Kispal, Brianna; Harris, Kristopher J.; O'Dell, Luke A.; Schurko, Robert W.
Abstract: 14 N ultra‐wideline solid‐state NMR (SSNMR) spectra were obtained for 16 naturally occurring amino acids and four related derivatives by using the WURST–CPMG (wideband, uniform rate, and smooth truncation Carr–Purcell–Meiboom–Gill) pulse sequence and frequency‐stepped techniques. The 14 N quadrupolar parameters were measured for the sp 3 nitrogen moieties (quadrupolar coupling constant, C Q, values ranged from 0.8 to 1.5 MHz). With the aid of plane‐wave DFT calculations of the 14 N electric‐field gradient tensor parameters and orientations, the moieties were grouped into three categories according to the values of the quadrupolar asymmetry parameter, η Q : low (≤0.3), intermediate (0.31–0.7), and high (≥0.71). For RNH3 + moieties, greater variation in N−H bond lengths was observed for systems with intermediate η Q values than for those with low η Q values (this variation arose from different intermolecular hydrogen‐bonding arrangements). Strategies for increasing the efficiency of 14 N SSNMR spectroscopy experiments were discussed, including the use of sample deuteration, high‐power 1 H decoupling, processing strategies, high magnetic fields, and broadband cross‐polarization (BRAIN‐CP). The temperature‐dependent rotations of the NH3 groups and their influence on 14 N transverse relaxation rates were examined. Finally, 14 N SSNMR spectroscopy was used to differentiate two polymorphs ofl ‐histidine through their quadrupolar parameters and transverse relaxation time constants. The strategies outlined herein permitted the rapid acquisition of directly detected 14 N SSNMR spectra that to date was not matched by other proposed methods. Abstract : A sensitive spy nucleus : Ultra‐wideline 14 N solid‐state NMR spectroscopy experiments on amino acids allow for the characterization of sp 3 ‐hybridized nitrogen sites and differentiation of polymorphs, as well as demonstrating the sensitivity of 14 N quadrupolar interactions to variations in hydrogen bonding.